Analisis Penanganan Kredit Macet Produk Kupedes PT Bank Rakyat Indonesia Unit Pasar Kembang - Yasinda Istiqomah; Irsyadul Ibad (Jurnal Riset Akuntansi, 2025)
This study aims to analyse the handling of bad debts on Kredit Umum Pedesaaan (KUPEDES) products at PT Bank Rakyat Indonesia Tbk Pasar Kembang Unit. As one of the units that provides financing for small businesses, BRI Unit Pasar Kembang faces challenges in managing the risk of bad credit, especially in the UMKM sector. Bad debts can occur due to the inability of debtors to meet their instalment payment obligations, which has the potential to reduce the bank's financial performance. This research applies a qualitative approach with data collection methods through interviews and direct observation in the field. The results showed that the handling of bad debts at BRI Unit Pasar Kembang was pursued through two main channels, namely non-litigation and litigation. In non-litigation, BRI takes a personal approach, gives warning letters, and administrative efforts such as rescheduling, reconditioning, and restructuring. If the non-litigation steps do not produce results, the handling continues through litigation by filing a lawsuit in court. The litigation process includes mediation and if no agreement is reached, execution of collateral can be carried out. This research provides an overview of the efforts made by BRI in managing bad debts and the importance of risk management to maintain the continuity of bank operations.